Formation mechanism of binary complex based on β-lactoglobulin and propylene glycol alginate with different molecular weights: Structural characterization and delivery of curcumin - Lin, Dongdong; Su, Jiaqi; Chen, Shuai; Wei, Jiao; Zhang, Liang; Li, Xiude; Yuan, Fang (Frontiers in Nutrition, 2022)
The complexation of protein and polysaccharide has shown considerable potential for the encapsulation of functional food components. In this work, propylene glycol alginate (PGA) molecules with different molecular weights (100, 500, 2000 kDa) were prepared through H2O2 oxidation, which were further combined with β-lactoglobulin nanoparticles (β-lgNPs) to form PGA-β-lgNPs complexes for the delivery of curcumin. Results showed that the depolymerization of PGA molecule was resulted from the breakage of glycosidic bonds in the main chain, and the depolymerization rate of PGA molecule depended on the reaction time, temperature, solution pH and H202 concentration. As the increasing molecular weight of PGA, the particle size, zeta-potential and turbidity of the complexes were obviously increased. The formation of PGA/β-lgNPs complexes was mainly driven by non-covalent interaction, including electrostatic gravitational interaction, hydrogen bonding and hydrophobic effect. Interestingly, the difference in the molecular weight of PGA also led to significantly differences in the micro-morphology of the complexes, as PGA with a high molecular weight (2000 kDa) generated the formation of a "fruit-tree" shaped structure, whereas PGA with relatively low molecular weight (100 and 500 kDa) led to spherical particles with a "core-shell" structure. In addition, the incorporation of PGA molecules into β-lgNPs dispersion also contributed to the improvement in the encapsulation efficiency as well as physicochemical stability of β-lgNPs, and PGA with a higher molecular weight was confirmed to exert a better effect. Findings in the current work may help to further understand the effect of molecular weight of polysaccharide on the physical and structural properties as well as effectiveness as delivery systems of polysaccharide-protein complexes, providing for the possibility for the design and development of more efficient carriers for bioactive compounds in food system.